Performance analysis of pharmaceutical installation as basic of feasibility: a self-based business unit into general services agency - Agus Yogeswara Wibawa, I Made; Wiksuana, I. G. B. (International research journal of management, IT and social sciences, 2019)
This study aims to determine the performance of the Pharmaceutical Installation as a basis for becoming an independent business unit in order to go to the Public Service Agency (BLU) at the Public Hospital in Denpasar, Bali. Performance measurement is a process of evaluating work progress against pre-determined goals and objectives and the results of activities are compared with the intended intentions; and the effectiveness of actions in achieving goals. In this study using a strategic mechanism in the form of a Balanced Score Card (BSC). Data collection techniques such as documentation, questionnaires, and observations. The data analysis technique used is the financial ratios for the financial perspective, the level of satisfaction for the customer perspective, the level of satisfaction for the perspective of growth and learning, while for the perspective of internal business processes using minimum service standards. The results of the 4 perspectives from the Balanced Scorecard show that the performance of the Pharmacy Installation at the Public Hospital in Denpasar is good and deserves to be an independent business unit.